The Impact of Competency and Work Motivation on Performance of Family Planning Extension Workers of BKKBN West Sumatra - Rivendri, Rivendri; Irmawita, Irmawita (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2025)
The backstory of this research is the low performance of Family Planning Extension Workers (PKB) BKKBN West Sumatra. The low performance of PKB is caused by competency factors and work motivation, where both factors are still relatively low. The purpose of this study are 1) To describe the competence of PKB. 2) To describe motivation. 3) To describe the performance of PKB. 4) To analyze the effect of competence on the performance of PKB. 5) To examine the effect of work motivation on performance. 6) To examine the effect of competence and work motivation on performance. This research uses a quantitative approach and correlational research type. Data were collected using a questionnaire. Data analysis techniques using Multiple Linear Regression. The results showed that: 1) PKB competence is in the sufficient category. 2) PKB work motivation is in the sufficient category. 3) PKB performance is in the sufficient category. 4) Work motivation has a significant effect on PKB performance. 5) Work motivation has a significant effect on PKB performance. 6) Competence and work motivation have a significant effect on PKB performance.